DIAGRAM DARI PRESENTASI SEMIGRUP 〈"a,b | " "a" ^"3" "=a," "b" ^"3" "=b,a" "b" ^"2" "=b" "a" ^"2" 〉 dan 〈"a,b | " "a" ^"5" "=a," "b" ^"5" "=b,a" "b" ^"2" "=b" "a" ^"2" 〉 - Wellya Aziz; Sri Gemawati; Asli Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
In this article we discuss the diagram forms of semigroup presentations    and . The discussion starts with the word-word outlines of semigroup presentations  and . Then it is proceeded to make a diagram of word-word description obtained. All of characteristics are expressed in the form of a semigroup diagram theorem. The discussion in this article refers to Guba, V.  & M. Sapir.  1996.  Diagram Groups and Robertson, E. F. & Y. Unlu. 1992. Proceedings of the Edinburgh Mathematical Society 36: 55 – 68.